Studi Fenomenologi: Psikologis Wanita Yang Menikah Muda Pada Masa Pandemi Covid-19 di Jawa Timur - Humayra' Nafisah Mar'atul Latif; Suryanto (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
Research on marriage has been very much done by previous researchers, including marriage at a young age. Young marriages referred to here are marriages carried out before the age recommended by the National Population and Family Planning Agency (BKKBN), which is 21 years for women and 25 years for men. When the Covid-19 pandemic entered Indonesia, the government carried out various restrictions to break the chain of this virus. This caused the Indonesian economy to decline drastically, but it actually made more and more teenagers marry at a young age. It is very interesting to study how the psychology of women who marry at a young age during the Covid-19 pandemic is very interesting. This study aims to determine the psychology of women who marry at a young age during the covid-19 pandemic, whether these women are happy or even experience stress and depression. This study uses a qualitative method with a phenomenological approach. Research participants are women who are married under the age of 21, married during the COVID-19 pandemic, live in East Java Province, and are willing to be involved in research. Data collection using semi-structured interviews. The results of this study indicate that women who married at a young age during the COVID-19 pandemic did not experience stress or depression and tended to be happy, so that the woman's psychology could be said to be healthy and good.